Prenatal microcephaly and hydrocephalus and normal heart anatomy, postnatal diagnosis of Nijmegen syndrome - Wójtowicz-Marzec, Monika; Respondek-Liberska, Maria (Prenatal Cardiology, 2018)
Nijmengen breakage syndrome is a rare autosomal condition mainly characterized by microcephaly. Patients are predisposed to malignancies due to combined immunodeficiency. The presented patient had prenatally diagnosed microcephaly with atypical ventriculomegaly of occipital horns. Fetal echocardiography showed a normal fetal heart anatomy. Diagnosis of Nijmengen syndrome was confirmed postnatally. The differential diagnosis of fetal microcephaly should take into account intrauterine infections, perinatal brain injury, congenital malformations or biological variants.